(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article provides information on education, independent improving the professional and pedagogical training of future teachers, independent education and requirements for it, abilities of students’ self-learning, independent education system, scientific - methodic basis of the stages and levels of assessment in the independent education system.